Digital innovation: transforming research and practice. Issue 1 (2nd January 2022) - Bogers, Marcel L. A. M.; Garud, Raghu; Thomas, Llewellyn D. W.; Tuertscher, Philipp; Yoo, Youngjin
ABSTRACT: There is no doubt that digital technologies are spawning ongoing innovation across most if not all sectors of the economy and society. In this essay, we take stock of the characteristics of digital technologies that give rise to this new reality and introduce the papers in this special issue. In addition, we also highlight the unprecedent opportunities that digital innovation provides to study innovation processes more generally. Overall, we conclude that the speed, observability, and relative ease in investigating relationships between multiple analytical levels, mean that digital innovation is both a 'model of' that also provides a 'model for' the study of innovation processes more broadly in non-digital and hybrid contexts.